Preparation method and application of PVDF-PVA piezoelectric sensing composite battery diaphragm

Through the PVDF-PVA voltage sensing composite battery diaphragm prepared by the coaxial static spinning legal system, the problem of hidden dangers of lithium-ion battery safety is solved, and effective monitoring and safety early warning of lithium-ion soft bag batteries is achieved.

CN119372839APending Publication Date: 2025-01-28HEFEI UNIV +1

Patent Information

Application Number
CN202411656306.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-28

Smart Images

  • Figure CN119372839A_ABST
    Figure CN119372839A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a PVDF-PVA piezoelectric sensing composite battery diaphragm, and relates to the technical field of new energy material preparation. The PVDF-PVA piezoelectric sensing composite battery diaphragm is prepared by taking poly (vinylidene fluoride-co-hexafluoropropylene), polyvinyl alcohol, N, N-dimethylformamide and acetone as raw materials and adopting a coaxial electrostatic spinning method, and the PVDF-PVA piezoelectric sensing composite battery diaphragm is simple in preparation process, mild in reaction condition and low in cost; the morphology of the obtained composite battery diaphragm can be controlled by adjusting the reaction temperature, the reactant proportion, the electrostatic spinning injection voltage, the flow speed, the injection distance and other process conditions, the specific surface area and the porosity of the diaphragm are increased through the specific nanofiber structure, and meanwhile PVDF serves as a positive electrode material of a friction material series to be paired with a negative electrode material PVA; the two circuits effectively generate piezoelectric sensing signals, so that the voltage generated when the soft package battery works is effectively detected, and timely and effective safety monitoring is carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy material preparation, and in particular to a preparation method and application of a PVDF-PVA piezoelectric sensing composite battery diaphragm. Background Art

[0002] Lithium-ion batteries are one of the most widely used secondary battery technologies, and are widely used in mobile devices, electric vehicles, energy storage systems, and other fields. However, there may be some safety hazards in the use of lithium-ion batteries, including but not limited to the following aspects: Overheating and combustion: Overcharging, over-discharging, or external short circuits may cause lithium-ion batteries to overheat or even catch fire. In extreme cases, this may cause the battery to explode, release toxic gases, and cause a fire; Mechanical damage: Once the outer shell of a lithium-ion battery is damaged, it may cause electrolyte leakage, which in turn causes a short circuit and overheating of the battery; Aging and cycle life: As the battery is used and the number of charge and discharge cycles increases, the electrode material will age, resulting in a decrease in battery performance and even safety hazards. In order to address the above safety hazards, researchers use a series of safety tests such as high-voltage electrical tests, thermal limit tests, and mechanical limit tests to monitor the safety of lithium-ion batteries.

[0003] Chinese patent application CN 117832754A discloses a diaphragm for lithium-ion batteries, a preparation method and application thereof. By using flexible piezoelectric PVDF as a diaphragm material for lithium-ion batteries, the driving force for the diffusion and deposition of lithium ions to the lithium nucleation and deposition site can be weakened by reverse overpotential during the operation of the lithium-ion battery, thereby effectively preventing the formation of lithium dendrites, while making the surface of the lithium metal negative electrode flat and reducing the battery capacity loss. Chinese patent application CN 111244364B discloses a PVDF-coated diaphragm, a preparation method thereof, and a lithium-ion battery. The PVDF coating contains PVDF composite particles so that the micropore size in the PVDF coating is consistent with the base film. Large-particle PVDF particles have supporting and pore-forming functions, small-particle PVDF particles provide the main bonding force between the diaphragm and the positive and negative pole pieces of the battery, and the binder bonds the coating to the base film. Thus, a specific proportion of PVDF composite particles keeps the micropore size in the coating consistent with the base film, reduces the internal resistance of the battery, and improves the cycle life and charge and discharge efficiency of the battery.

[0004] The two PVDF diaphragms mentioned above only mention their effects on improving the battery cycle life and charge and discharge efficiency of lithium-ion batteries, and there is no in-depth research on the piezoelectric sensing properties of PVDF diaphragms and monitoring the internal pressure of lithium-ion batteries. Summary of the invention

[0005] In view of the problems in the prior art, the purpose of the present invention is to provide a method for preparing a PVDF-PVA piezoelectric sensing composite battery diaphragm, and apply the prepared PVDF-PVA piezoelectric composite battery diaphragm to lithium-ion soft-pack batteries, which can effectively monitor the changes in pressure during the operation of lithium-ion soft-pack batteries.

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing a PVDF-PVA piezoelectric sensing composite battery diaphragm comprises the following steps:

[0008] Step S1: dissolving poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) powder in acetone (AC) and N,N-dimethylformamide (DMF), and stirring to obtain solution A; dissolving polyvinyl alcohol (PVA) powder in deionized water, and stirring to obtain solution B;

[0009] Step S2: using solution A as the electrospinning shell layer spinning solution and solution B as the electrospinning core layer spinning solution, and adopting coaxial electrospinning technology to prepare an electrospinning composite membrane;

[0010] Step S3: placing the obtained diaphragm in a vacuum drying oven, and obtaining a PVDF-PVA piezoelectric sensing composite battery diaphragm after drying.

[0011] As a further preferred technical solution of the present invention, in the preparation method:

[0012] The weight ratio of the poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) powder to the polyvinyl alcohol (PVA) powder is 0.1-1:0.1-1, and the volume ratio of acetone (AC) to N,N-dimethylformamide (DMF) in solution A is 1-3:7-9. In step S1, the mass fraction ratio of the poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) powder in solution A is 10-15wt%, and the mass fraction ratio of the polyvinyl alcohol (PVA) powder in solution B is 8-12wt%. When the shell spinning solution A is prepared by stirring, the temperature is room temperature and the stirring time is 5-10h; when the core spinning solution B is prepared by stirring, the temperature is 80-100°C and the stirring time is 10-15h.

[0013] The coaxial electrospinning process parameters in step S2 are: the electrospinning voltage is set to 18 kV, the core layer spinning solution flow rate is 0.2-0.5 mL / h, the shell layer spinning solution flow rate is 0.3-0.6 mL / h, the rotation speed is 320 rpm, and the distance between the transmitter and the receiving substrate is 15 cm.

[0014] In step S3, the drying temperature is 90-110° C. and the drying time is 10-15 hours.

[0015] The second object of the present invention is the PVDF-PVA piezoelectric sensing composite battery diaphragm obtained according to the aforementioned preparation method, the thickness of the composite battery diaphragm is 40 to 60 μm, and the microstructure of the composite battery diaphragm is composed of dense and bead-free nanofibers with an average diameter of 200 nm.

[0016] The third object of the present invention is to provide the use of the aforementioned PVDF-PVA piezoelectric sensing composite battery separator as a lithium ion soft pack battery separator.

[0017] The fourth object of the present invention is to provide the aforementioned PVDF-PVA piezoelectric sensing composite battery separator for use as a safety monitoring device for lithium-ion soft-pack batteries. PVDF is used as the positive electrode material of the friction material series and is paired with the negative electrode material PVA. Both effectively generate piezoelectric sensing signals, thereby effectively detecting the voltage generated when the soft-pack battery is working, and performing timely and effective safety monitoring.

[0018] The beneficial effects of the present invention are specifically shown as follows:

[0019] 1. The present invention uses poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), polyvinyl alcohol (PVA), N,N-dimethylformamide (DMF) and acetone as raw materials, and adopts a coaxial electrospinning method to prepare a nanofiber PVDF-PVA piezoelectric sensing composite battery separator. The preparation process is simple, the reaction conditions are mild, and the cost is low. The morphology of the obtained PVDF-PVA composite battery separator can be controlled by adjusting the reaction temperature, the ratio of reactants, and the electrospinning spray voltage, flow rate, spray distance and other process conditions.

[0020] 2. The PVDF-PVA piezoelectric sensing composite battery diaphragm prepared by the present invention has good uniformity, and its nanofiber structure has an average diameter of 200nm and a large specific surface area. Compared with ordinary commercial polypropylene PP diaphragms, the PVDF-PVA diaphragm has more excellent liquid absorption rate and porosity, which not only improves the transmission efficiency of ion electrolytes, but also can form a larger electrolyte storage layer; at the same time, PVDF is paired with the negative electrode material PVA as the positive electrode material of the friction material series, and the two effectively generate piezoelectric sensing signals, thereby effectively detecting the voltage generated when the soft-pack battery is working, and performing timely and effective safety monitoring.

[0021] 3. The PVDF-PVA piezoelectric sensing composite battery diaphragm prepared by the present invention can be applied to the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of the core-shell structure of the PVDF-PVA piezoelectric sensing composite battery diaphragm prepared in Example 1 of the present invention.

[0023] Figure 2 This is a comparison chart of X-ray diffraction of the coaxial electrospun PVDF-PVA piezoelectric sensing composite battery diaphragm, single-spun PVDF diaphragm, and single-spun PVA diaphragm prepared in Example 1 of the present invention.

[0024] Figure 3 These are low (a) and high (b) magnification scanning electron micrographs of the PVDF-PVA piezoelectric sensing composite battery separator prepared in Example 1 of the present invention.

[0025] Figure 4 This is a comparison chart of the porosity (a) and liquid absorption rate (b) of the PVDF-PVA piezoelectric sensing composite battery diaphragm and the PP diaphragm prepared in Example 1 of the present invention.

[0026] Figure 5 The piezoelectric performance test of the PVDF-PVA piezoelectric sensing composite battery diaphragm prepared in Example 1 of the present invention as a composite diaphragm for lithium-ion soft-pack batteries is shown, and the voltage signal curves are obtained under conditions of increasing pressure (a) and constant pressure (b).

[0027] Figure 6 These are the actual pictures of the PVDF-PVA piezoelectric sensing composite battery diaphragm prepared in Example 1 of the present invention used as a composite diaphragm for lithium-ion soft-pack batteries before (a) and after (b) lighting a small light bulb. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with embodiments and drawings.

[0029] Example 1

[0030] A method for preparing a PVDF-PVA piezoelectric sensing composite battery diaphragm comprises the following steps:

[0031] Step S1: 0.6248 g of poly(vinylidene fluoride-co-hexafluoropropylene) was added to a mixed solution of 4 mL of N,N-dimethylformamide and 1 mL of acetone, and stirred evenly at room temperature for 8 h to obtain a shell spinning solution A with a solid content of 12 wt%. 0.6818 g of polyvinyl alcohol was added to 5 mL of deionized water, and stirred evenly at 90° C. for 12 h to obtain a core spinning solution B with a solid content of 10 wt%.

[0032] Step S2: Slowly add the spinning solution A and the spinning solution B prepared in step S1 into two 10mL syringes respectively, and connect the two spinning solutions to the shell layer and the core layer of the coaxial electrospinning needle respectively, the core layer spinning solution flow rate is 0.2-0.5mL / h, and the shell layer spinning solution flow rate is 0.3-0.6mL / h; a rotating cylinder covered with aluminum foil is used as a receiving device, and its rotation speed is 320rpm, and a spinning distance of 15cm is set between the tip of the syringe and the collector; the spinning solution passes through the spinneret, and the fiber is stretched by the high-voltage electrostatic electric field, wherein the electrostatic voltage used is 18kV; when the solvent evaporates, a coaxial electrospinning composite diaphragm is obtained on the receiving device.

[0033] Step S3: Take the diaphragm obtained in the above step S2 and place it in a vacuum drying oven at 100° C. overnight, and then take it out to obtain a PVDF-PVA piezoelectric sensing composite battery diaphragm.

[0034] from Figure 1 It can be seen that the prepared composite battery separator has a core-shell structure, with polyvinyl alcohol as the core layer and poly(vinylidene fluoride-co-hexafluoropropylene) as the shell layer.

[0035] The single-spinning PVDF membrane and single-spinning PVA membrane were prepared by traditional methods and tested. Figure 2 It can be seen that the X-ray diffraction peak of the PVDF-PVA piezoelectric sensing composite battery separator prepared in Example 1 has only the characteristic peak of PVDF-HFP, indicating that a core-shell structure with PVDF-HFP as the shell and PVA as the core layer is successfully synthesized.

[0036] from Figure 3 It can be seen that the PVDF-PVA piezoelectric sensing composite battery separator prepared in Example 1 is in the form of nanofibers with an average diameter of 200 nm, and its microstructure is dense and free of beads.

[0037] from Figure 4 It can be seen that the PVDF-PVA piezoelectric sensing composite battery diaphragm prepared in Example 1 has a better porosity and liquid absorption rate than the traditional PP diaphragm, which are increased by 110.63% and 273.09% respectively.

[0038] from Figure 5 It can be seen that the PVDF-PVA piezoelectric sensing composite battery diaphragm prepared in Example 1 generates a relatively regular piezoelectric signal under regular pressure. Figure 5 (a) is the voltage signal obtained under the condition of increasing applied pressure, Figure 5 (b) is the voltage signal obtained under the condition of applying the same pressure.

[0039] A mixed solution of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) (volume ratio 1:1:1) dissolved with 1 mol / L lithium hexafluorophosphate was used as the electrolyte of the lithium ion soft pack battery, and the lithium ion soft pack battery was assembled using the composite battery separator prepared in Example 1. The result obtained was as follows: Figure 6 As shown, the small light bulb can be lit. It can be seen that the PVDF-PVA piezoelectric sensing composite battery separator can effectively monitor the pressure changes generated inside the lithium-ion soft-pack battery during operation.

[0040] In summary, the PVDF-PVA piezoelectric sensing composite battery diaphragm prepared by the present invention has a microstructure composed of dense and bead-free nanofibers, and the average diameter of the nanofibers is 200nm. Compared with the traditional PP diaphragm, the PVDF-PVA piezoelectric sensing composite battery diaphragm prepared by the present invention has a higher liquid absorption rate and porosity. In addition, the PVDF-PVA piezoelectric sensing composite battery diaphragm can effectively monitor the changes in the internal pressure of the soft-pack battery during operation, and then make timely safety warnings.

[0041] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a PVDF-PVA piezoelectric sensing composite battery diaphragm, characterized in that: The following steps are involved: Step S1: dissolving poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) powder in acetone (AC) and N,N-dimethylformamide (DMF), and stirring to obtain solution A; dissolving polyvinyl alcohol (PVA) powder in deionized water, and stirring to obtain solution B; Step S2: using solution A as the electrospinning shell layer spinning solution and solution B as the electrospinning core layer spinning solution, and adopting coaxial electrospinning technology to prepare an electrospinning composite membrane; Step S3: placing the obtained diaphragm in a vacuum drying oven, and obtaining a PVDF-PVA piezoelectric sensing composite battery diaphragm after drying.

2. The preparation method according to claim 1, characterized in that: The weight ratio of the poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) powder to the polyvinyl alcohol (PVA) powder is 0.1-1:0.1-1, and the volume ratio of acetone (AC) to N,N-dimethylformamide (DMF) in solution A is 1-3:7-9.

3. The preparation method according to claim 2, characterized in that: In step S1, the mass fraction ratio of poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) powder in solution A is 10-15wt%, and the mass fraction ratio of polyvinyl alcohol (PVA) powder in solution B is 8-12wt%.

4. The preparation method according to claim 1, 2 or 3, characterized in that: When the shell spinning solution A is prepared by stirring, the temperature is room temperature and the stirring time is 5 to 10 hours; when the core spinning solution B is prepared by stirring, the temperature is 80 to 100° C. and the stirring time is 10 to 15 hours.

5. The preparation method according to claim 1, characterized in that: The coaxial electrospinning process parameters in step S2 are: the electrospinning voltage is set to 18 kV, the core layer spinning solution flow rate is 0.2-0.5 mL / h, the shell layer spinning solution flow rate is 0.3-0.6 mL / h, the rotation speed is 320 rpm, and the distance between the transmitter and the receiving substrate is 15 cm.

6. The preparation method according to claim 1, characterized in that: In step S3, the drying temperature is 90-110° C. and the drying time is 10-15 hours.

7. The PVDF-PVA piezoelectric sensing composite battery separator prepared by the method according to any one of claims 1 to 6, characterized in that: The thickness of the composite battery separator is 40 to 60 μm, and the microstructure of the composite battery separator is composed of dense and bead-free nanofibers with an average diameter of 200 nm.

8. Application of the PVDF-PVA piezoelectric sensing composite battery separator as claimed in claim 7 as a separator for lithium-ion soft-pack batteries.

9. The use according to claim 8, characterized in that: PVDF is paired with PVA as the positive electrode material of the friction material series. The two effectively generate piezoelectric sensing signals, thereby effectively detecting the voltage generated when the soft-pack battery is working, and conducting timely and effective safety monitoring.

Citation Information

Patent Citations

  • A PVDF-coated separator and its preparation method, and a lithium-ion battery.

    CN111244364B

  • Diaphragm for lithium ion battery as well as preparation method and application of diaphragm

    CN117832754A

  • Polyvinylidene-fluoride-based composite fibrous membrane, preparation method and application thereof

    CN103147224A

  • Fibrous flexible rechargeable zinc-manganese battery based on multivalent manganese oxide

    CN110534816A

  • Preparation method of electrospun fiber diaphragm with excellent mechanical property

    CN110983629A

Cited By

  • PVDF-PMMA piezoelectric sensing composite diaphragm as well as preparation method and application thereof

    CN122552740A